Scimitar Syndrome Issued from a Consanguineous Marriage: A Rare Congenital Cardiomyopathy - Rihab Machtache; Soukaina Safir; Sara Chibane; Abdenasser Drighil; Leila Azzouzi; Rachida Habbal; Fadoua Kossale; Pr Salam (Publisher: Shahid Beheshti University of Medical Sciences)
We present here a rare case of Scimitar syndrome on a full-term newborn female issued from consanguineous marriage and diagnosed at the age of two months who was suffering from polypnea since the age of two weeks. She was admitted at the age of two months for polypnea, non-dysmorphic facies, healthy systemic arterial tension, regular pulse, but the family history raises that before her birth, two newborns respectively boy and girl died both at an early age with dilated cardiomyopathy. After hospitalization, we realized chest radiography, which has shown opaque right lung and suspicion of scimitar syndrome. After that, an echocardiogram was performed, showing severe hypoplasia of the right pulmonary artery with pulmonary hypertension. The Thoracic computed tomography confirmed the diagnosis by revealing hypoplasia of the right pulmonary artery with pulmonary arterial hypertension, right pulmonary hypoplasia (bilobar), and abnormal partial right pulmonary venous return toward the vena cava under the diaphragm.